Pengaruh Corporate Governance dan Auditor Eksternal dalam Pencegahan Kecurangan Menggunakan Model Beneish dan Model OMI - Amalia Crisma Indah; Fauzan Misra (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
Fraud cases have occurred since 2001. This has an impact on the decline in the world economy. In 2019, there was another decline in the world economy due to the Covid-19 outbreak which had an impact on reducing the quality of company financial reports. To prevent a decline in the quality of company financial reports which results in increased fraud, corporate governance and the quality of a company's external auditors must be improved. This study aims to empirically examine the role of corporate governance attributes, consisting of boards of directors, commissioners, audit committees, and institutional ownership, as well as the role of the quality of external auditors which is proxied by differences in Big 4 and Non Big 4 auditors in fraud prevention. The research sample is non-financial companies listed on the Indonesia Stock Exchange (BEI) during the 2017-2021 period, with observations of 307 companies. The regression method used to test the hypothesis is, the Beneish Model uses the logistic regression method with the help of SPSS ver 21 and the OMI Model uses the OLS regression method with the help of Eviews 12. The results of the research between the two regression models are that only the external auditor quality variable has a significant relationship with prevention. fraud. However, when tested using the logistic regression method, the variables that are significant in preventing fraud are institutional ownership and the quality of external auditors. Meanwhile, when tested using the OLS regression method, the research results showed that the variable that was significant in preventing fraud was the quality of the external auditor. So the use of the OMI Model in this research can strengthen the probability results of the Beneish Model to measure fraud in a company.